Viewpoints of Educational and Clinical Staff in Shiraz University of Medical Sciences to Barriers Implementation of Evidence-Based Care - A.M. Parvinia Nasab; M.A. Vojdani; A. Dehghani; Z. Keshtkaran; A. Kavosi (Bihdād, 2014)
Background and Aims: Naturally, it is expected that health system services be evidence-based, methods and scientific decision making. There has been a wide gap between the practice-based nursing and research-based nursing evidence in Iran. Therefore, this study is an endeavor to investigate barriers to implement evidence-based care among educational and clinical Staff Materials & Methods: This descriptive cross-sectional study was conducted upon 40 (academic Staff) and 70(clinical staff) in different ward of Namazi Hospital and Academic Staff of Shiraz University of Medical Science who were selected by simple random sampling method. Instrument used for study was demographic questionnaire and questionnaire barriers of lack of implementation Evidence -based care. Data were analyzed using SPSS. Results: From the viewpoints of clinical staff, lack of enough human resources with 87.1%, lack of sufficient awareness about the necessity of evidence-based with 85.5% and From the viewpoints of academic staff lack of enough human resources with 82.5% and lack of trained people how to use research finding in evidence-based care with 77.5% was mentioned as an important obstacle Conclusion: Lack of clinical staff, lack of enough human resources and lack of sufficient awareness was mentioned as an important obstacle, Therefore it is recommended to pay more attention to this subject through holding educational workshops and meetings, and to have more interaction and cooperation with centers which implement evidence-based care and make use of their life experiences according to existing facilities.